Implikasi pemilihan kepala daerah langsung terhadap kehidupan demokrasi di daerah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Throughout the history of regional government regulation, determining a Regional Head is mostly done in an appointing mechanism by the central government. Although the candidate is being nominated by the Regional House of Representatives (DPRD), he is not in the capacity of giving definitive decision. The Law Number 22 of 1999 changes the centralistic mechanism by giving full authority to DPRD to determine the Regional Head and to ask for his responsibility as well. This powerful authority gives the DPRD elitist horizontal attitude. Local democracy vis a vis local centralization. Regional Head direct election is considered a solution to the problem of local democracy. It allows the public to participate and also builds check and balances mechanism between DPRD and the Regional Head. Key words: Direct election â democratic